2007
DOI: 10.1093/aje/kwm061
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and the Development of Type 2 Diabetes in a Community-based Longitudinal Study

Abstract: The temporal relation of hepatitis C virus (HCV) infection to the development of type 2 diabetes remains unknown. The authors followed 4,958 persons aged > or =40 years without diabetes (3,486 seronegative, 812 anti-HCV+, 116 with hepatitis B virus/HCV coinfection, and 544 hepatitis B surface antigen (HBsAg)+) from a community-wide cohort in southern Taiwan for 7 years (1997-2003) to study the risk of diabetes associated with HCV infection. A total of 474 participants developed diabetes. The 7-year cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
109
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 35 publications
9
109
2
3
Order By: Relevance
“…Mehta et al, in their study did conclude that amongst patients with HCV related liver disease, the incidence of DM was higher in those who were older and those who had a high BMI [23]. A study conducted in Taiwan by Wang et al, showed that the risk ratio for diabetes in anti-HCV positive patients increased when BMI levels increased [26]. Our study also revealed that increase in the BMI increases the prevalence of impaired glucose tolerance.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Mehta et al, in their study did conclude that amongst patients with HCV related liver disease, the incidence of DM was higher in those who were older and those who had a high BMI [23]. A study conducted in Taiwan by Wang et al, showed that the risk ratio for diabetes in anti-HCV positive patients increased when BMI levels increased [26]. Our study also revealed that increase in the BMI increases the prevalence of impaired glucose tolerance.…”
Section: Discussionsupporting
confidence: 58%
“…It was found that the maximum number of patients with impaired glucose tolerance were in the age group 60-69 y (13 patients). Mason et al, [13] and Wang et al, [24,26] also studied correlation of gender with IGT/DM and found that gender did not have significant influence on the development of diabetes. However, our study revealed that females did have a significantly higher prevalence of impaired glucose tolerance (14 out of 22 females v/s 26 out of 78 males).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies support an association between chronic HCV hepatitis and type DM2 as the primary predisposing factor being insulin resistant (IR) (24)(25)(26)(27). According to Mehta and cols.…”
Section: Discussionmentioning
confidence: 99%
“…(2000), subjects who are more than 40 years old and have anti-HCV antibodies have a 3.77 fold higher risk of developing DM2, compared with those who were anti-HCV negative, matched for gender, BMI and ethnic background (27). Although liver cirrhosis (regardless of etiology) has been associated with the development of IR and DM2, chronic HCV infection is reported to be more strongly related with the development of IR than chronic HBV hepatitis (26). In our study, from 82 patients, 22 (27%) had serum HOMA-IR levels greater than 2.5, which is consistent with IR diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients whose fasting blood glucose levels were >115 mg/dl were selected. 70 patients were recruited for study group and 35 patients were recruited for control group, in the ratio of 2:1 [51][52][53][54][55][56][57][58][59][60].…”
Section: Sample Size Determination and Sampling Techniquementioning
confidence: 99%